Work, family and well-being in five North- and East-European capitals - Haavio-Mannila, Elina (Suomalainen Tiedeakatemia, 1992)
In this study quality and conditions of work, social relations in the workplace and in the family, and well-being of engineers, teachers, and workers will be compared in three Nordic capitals: Copenhagen (Denmark), Helsinki (Finland), and Stockholm (Sweden); and in two capitals which at the time of the data gathering belonged to the Soviet Union: Tallin in Estonia and Moscow in Russia.
Includes bibliographical references (p. 113-117)
Keywords: Graue Literatur; Quality of work life; Europe; Northern; Europe; Eastern; Work environment; Work; Arbeit; Familie; Sozialer Indikator; Großstadt; Kopenhagen; Helsinki; Stockholm; Moskau; Tallinn